2009
DOI: 10.1128/aac.00886-08
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Plasmid-Mediated Quinolone Resistance Determinants qnr , aac(6) - Ib-cr , and qepA among Ceftiofur-Resistant Enterobacteriaceae Isolates from Companion and Food-Producing Animals

Abstract: Three kinds of plasmid-mediated quinolone resistance (PMQR) determinants have been discovered and have been shown to be widely distributed among clinical isolates: qnr genes, aac(6)-Ib-cr, and qepA. Few data on the prevalence of these determinants in strains from animals are available. The presence of PMQR genes in isolates from animals was determined by PCR amplification and DNA sequencing. The production of extended-spectrum ␤-lactamases (ESBLs) and AmpC ␤-lactamases in the strains was detected, and their ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(146 citation statements)
references
References 40 publications
7
131
3
4
Order By: Relevance
“…7,8,12,20 To our knowledge, this study is the first report of qnrA 1 , qnrS 2 , aac(6¢)-Ib-cr and qepA genes in S. flexneri (the nucleotide sequence reported herein has been registered with the EMBL database under accession nos. FJ177519, FJ177521, FJ949571, FJ842530, respectively).…”
Section: Molecular Typing Of Bacterial Dnamentioning
confidence: 99%
“…7,8,12,20 To our knowledge, this study is the first report of qnrA 1 , qnrS 2 , aac(6¢)-Ib-cr and qepA genes in S. flexneri (the nucleotide sequence reported herein has been registered with the EMBL database under accession nos. FJ177519, FJ177521, FJ949571, FJ842530, respectively).…”
Section: Molecular Typing Of Bacterial Dnamentioning
confidence: 99%
“…About 75.8% of the strains possess ST15-CTX-M-15, which is a clonal group that emerged in humans in recent times and this strain shared PFGE clusters with human isolates, signifying the dissemination of this clonal group between human and animal populations (Ewers et al, 2014).There are reports of ESBL in other Enterobacteriaceae members like Enterobacter sp., K. pneumoniae, Citrobacter sp. and Salmonella enterica serovar Newport (Haenni et al, 2012;Ma et al, 2009). A recent study conducted in Netherlands reported a high prevalence of faecal carriage of Enterobacteriaceae resistant to third-generation cephalosporins in cats and dogs (Hordijk et al, 2013).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…This new PMQR mechanism is still very rare, except ESBL genes in the Moroccan community in China where recent studies underlined the predominance of the qepA gene in enterobacterial strains isolated from food-producing animals (Ma et al, 2009). The now common combination of CTX-M-15, OXA-1, SHV-1 and TEM-1 b-lactamases and PMQR determinants aac(69)-Ib-cr and qnrS1 in a community K. pneumoniae strain (K.p18), as reported here, is, to our knowledge, a first.…”
Section: A Barguigua and Others 1348mentioning
confidence: 99%